Virus : an illustrated guide to 101 incredible microbes - Roossinck, Marilyn J. (Princeton University Press, 2016)
This stunningly illustrated book provides a rare window into the amazing, varied, and often beautiful world of viruses. Contrary to popular belief, not all viruses are bad for you. In fact, several are beneficial to their hosts, and many are crucial to the health of our planet. Virus offers an unprecedented look at 101 incredible microbes that infect all branches of life on Earth--from humans and other animals to insects, plants, fungi, and bacteria.- Resumé vydavatel
Keywords: viry; virologie; viruses; virology; elektronické knihy; přehledy; electronic books; surveys